Limited knowledge of health risks along the illegal wild meat value chain in the Nairobi Metropolitan Area (NMA) - Masudi, Sherril P.; Hassell, J.; Cook, Elizabeth A.J.; Hooft, P. van; Langevelde, F. van; Buij, R.; Otiende, M.Y.; Ochieng, J.W.; Santangeli, A.; Happi, A.; Akpan, S.N.; Thomas, Lian F. (2025)
Consumption of and trade in wild meat could result in infectious pathogen spillover into human populations. Such spillovers could propagate into sustained outbreaks in major cities where human aggregations potentially catalyze their spread. A better understanding of how urban wild meat value chains operate could assist in mitigating spillover events. We used key informant interviews and literature review to understand the structure and operations, actors, their practices, and health risk perceptions along a wild meat value chain supplying a rapidly urbanizing city in Africa, the Nairobi Metropolitan Area (NMA). The value chain operates via three main nodes: harvester, trader, and consumer nodes. We found wild meat to be harvested from peri-urban areas of the NMA, consumed or sold locally, or supplied to distant urban markets. Actors reported increased participation along the value chain during the dry season, and over the Christmas period. The value chain operated informally, creating a ‘rules in use’ framework focusing on sanction avoidance, while ignoring food safety concerns. Consequently, respondents reported slaughtering wild animals on the bare ground, handling wild meat with unwashed hands and uncleaned utensils. No value chain actors reported wearing personal protective equipment when handling wild meat. At the distant markets’ trader node where wild meat was sold as livestock meat, meat vendors engaged in similar unsafe practices. Actors had limited awareness of the specific health risks from wild meat. We speculate that the observed limited health risk awareness, and sanction avoidance attempts promotes unsafe practices during exploitation of wild animals for food, income and for medicinal purposes. Multisectoral efforts at the conservation and public health nexus, as well as community education on the potential health risks from wild meat are key in reducing potential spillovers.